Vaccination rate and adherence of tick-borne encephalitis vaccination in Germany. Issue 5 (29th January 2021) - Schley, Katharina; Malerczyk, Claudius; Beier, Dominik; Schiffner-Rohe, Julia; von Eiff, Christof; Häckl, Dennis; Süß, Jochen
Highlights: Results show very low TBE vaccination uptake in Germany. Vaccination uptake is higher in southern Germany. Adherence to the vaccination schedule declines with each subsequent vaccination. Simulated vaccination protection ranges from 10% to 51%, by federal state. Abstract: Background: Tick-borne encephalitis (TBE) is an arboviral infection of the central nervous system. As there is no causal treatment of TBE, disease prevention by vaccination is especially important. Immunization consists of a three-dose primary vaccination schedule, followed by regular booster doses. In Germany, the Standing Committee on Vaccination (STIKO) at the Robert Koch-Institute recommends TBE vaccination for all those at high risk of contracting TBE. This includes individuals living in, traveling to and/or working in risk areas, and being exposed to ticks. To our knowledge, there are currently no reliable data on TBE vaccination rates in Germany available. Methods: This retrospective cohort study based on anonymized German health claims data was conducted to determine vaccination rates of TBE primary immunization in 2012 to 2015 by federal state, compliance with the vaccination schedule, and TBE vaccination uptake for the 2011 birth cohort. Vaccination protection rates for each federal state were simulated based on a compartmental model. Results: Vaccination rates of an initiated primary immunization ranged from about 3% in the southern federal states to <1% in the northern federal states. Across all federal states, compliance with the vaccination schedule decreased with each subsequent vaccination. Slightly higher TBE vaccination uptake was determined in the 2011 birth cohort, as compared to the German school entry health examination statistics in 2017. Simulated vaccination protection rates for each federal state ranged from 10% in Hamburg to 51% in Baden-Wuerttemberg. Conclusions: While there was an overall low vaccination uptake and a discrepancy between areas of high vs. low TBE risk, this study also indicates a concerning decline in vaccination compliance. Vaccinating physicians should address the importance of adherence upon initiation of TBE vaccination.